Bloom syndrome: multiple retinopathies in a chromosome breakage disorder. Issue 3 (20th February 2004) - Bhisitkul, R B; Rizen, M
Abstract : Aim: To describe multiple retinal abnormalities in a patient with Bloom syndrome, including early macular drusen, diabetic retinopathy, and the onset of leukaemic retinopathy. Methods: Clinical data were collected over 1 year of follow up, and ocular abnormalities in Bloom syndrome were reviewed from the literature. Results: A 39 year old man with a rare autosomal recessive "chromosome breakage" syndrome was followed. A variety of ocular findings have been reported in Bloom syndrome; this patient had hard drusen in both maculae, non-proliferative diabetic retinopathy, and haemorrhagic retinopathy as a herald of acute lymphocytic leukaemia. Conclusions: Bloom syndrome is a rare disorder of genomic instability, in which a variety of ocular abnormalities have been found. Described here are multiple retinal manifestations arising from characteristic systemic associations of diabetes mellitus and leukaemia, as well as macular hard drusen.